2022
DOI: 10.1111/ijfs.15684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the proteins of indica rice and indica waxy rice on the formation of volatiles of sweet rice wine

Abstract: Summary The proteins in the raw materials affect the formation of flavour during fermentation. Among all the fermentation broth of protein fraction in the study, the rice prolamin and albumin effectively promoted floral, honey and fruity characteristics in fermentation with higher level of β‐phenylethyl alcohol, 2,4‐dimethyl‐benzaldehyde and ethyl hexadecanoate than those in the fermentation of globulin and glutelin; albumin is with higher level of higher alcohols, but higher alcohols are not good for health b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…However, the effect of protein components on reducing sugar content was found to be non-significant, though these values were still within the same range as concentrations reported in previous studies on traditional millet Huangjiu [ 10 , 12 ]. Similar findings were also reported in rice Huangjiu and sake [ 8 , 9 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…However, the effect of protein components on reducing sugar content was found to be non-significant, though these values were still within the same range as concentrations reported in previous studies on traditional millet Huangjiu [ 10 , 12 ]. Similar findings were also reported in rice Huangjiu and sake [ 8 , 9 ].…”
Section: Resultssupporting
confidence: 89%
“…Previous research has suggested that the production of bitter peptides in sake is highly dependent on the glutelin content of rice grains [ 8 ], highlighting the significance of protein metabolism in shaping the flavor profile of fermented beverages. The development of bitterness in Huangjiu is thought to arise from an imbalance in protein hydrolysis and peptide hydrolysis, emphasizing the importance of carefully balancing the glutelin contents in raw materials to optimize wine quality [ 4 , 6 , 9 ]. Taken together, these findings suggest that carefully selecting the appropriate protein type and amount during the fermentation process is essential to achieving the desired taste profile in millet Huangjiu.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinese sweet rice wine (CSRW) is a traditional beverage consumed in China and prized by consumers for its unique flavor and purported nutritional properties related to its enrichment with oligosaccharides, polypeptides, vitamins, minerals, and amino acids [1]. CSRW is generally brewed with glutinous rice and has a low alcohol content, ranging from 0.5% to 14% (v/v), with a savory sweet taste that differs from Chinese yellow rice wine, which is brewed with rice or millet and has a higher alcohol content of 14-20% (v/v) [2,3]. In addition, CSRW fermentation also requires the addition of specific fermentation starters, also known as Jiuqu.…”
Section: Introductionmentioning
confidence: 99%